Ultrasound validity in the measurement of knee cartilage thickness. Issue 8 (6th August 2008) - Naredo, E; Acebes, C; Möller, I; Canillas, F; de Agustín, J J; de Miguel, E; Filippucci, E; Iagnocco, A; Moragues, C; Tuneu, R; Uson, J; Garrido, J; et al.
Abstract : Objective: To assess the multiexaminer reproducibility and the accuracy comparing with cadaver anatomic specimens of ultrasound (US) measurement of femoral articular cartilage (FAC) thickness. Methods: In 8 flexed cadaver knees, FAC thickness was blindly, independently and consecutively measured twice by 10 rheumatologists at the lateral condyle (LC), medial condyle (MC) and intercondylar notch (IN) with US. After the US measurements, the knees were dissected. Articular cartilage integrity was evaluated macroscopically in the femoral condyles. FAC thickness was blindly measured in the specimens using a stereoscopic magnifying loupe and a digitised image software. Interexaminer and intraexaminer reliability of US FAC thickness measurement and agreement between US and anatomic measurements were assessed by estimating the intraclass correlation coefficient (ICC). Results: Interexaminer ICCs were higher than 0.90 for MC (p<0.001) and IN (p<0.001) and higher than 0.75 for LC (p<0.01). Mean intraexaminer ICCs were 0.832 for MC (p<0.001), 0.696 for LC (p<0.001) and, 0.701 for IN (p<0.001). Agreement between US and anatomic FAC thickness measurements was good for MC (ICC 0.719; p = 0.020) and poor for LC (p = 0.285) and IN (p = 0.332). Bland–Altman analysis showed that the difference between US and anatomic values was considerably high in the one knee with severely damaged FAC. After eliminating this knee from the analysis, ICCs were 0.883 (p<0.001) for MC, 0.795 (p = 0.016) for LC and 0.732 for IN (p = 0.071). Conclusion: US demonstrated a good reproducibility in FAC thickness measurement by multiple examiners. In addition, US FAC thickness measurement was accurate in normal to moderately damaged cartilage.